Canada : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper explores the factors that have led to a Canada-U.S. productivity gap using a sectoral growth accounting approach. Both fiscal and monetary policies have had significant effects on the saving rate. The Canadian dollar's appreciation was followed by a protracted period of exchange rate weakness. This paper reviews the institutional aspects of Canada's real return bond program. The Canadian system provides a successful model for pension reform. Free trade has helped promote the integration of U.S. and Canadian economies, but significant differences remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet